أثر مدرسة التجديد في آراء العلامة ملا محمد الجليزاده من ناحية منهجه التفسيري مستل من رسالة ماجستير - كريم, حسين حسن; صالح, عبدالله عزيز حمه (Sulaimani Journal for Humanities, 2022)
After Reading this research we reach this results: That time which Mula Muhamad Jalizada-Malay Gawrai Koya- lives it, It’s not stability from political and social dimensions. Malay Gawra is one of most prominent Kurdish Scientists which served Islam religion and Science, but is most prominent Kurdish intellectual in its time. In spite of interpretation of Malay Gawra –Kurdish Interpretation to Word of God- don’t free of Mathur interpretation, but we can say Malay gawra interpretation is acceptable Mathur interpretation type which character and independence of interpreter seemed completely in this type of interpretation , but even some times defended from opinion against another opinion by evidence. Malay gawra had effected by some of renovated scientists of its era, such as -Muhamad Abdo, Muhamad Rashid Rida ,but not received all what their saying , but occasionally Criticized their view and respond their opinion, so we can say if Malay Gawra wrote its interpretation by Arabic don’t less anything of (Muhamad Abdo, Muhamad Rashid Rida) interpretation, but in some places progressed them, Malay gawra wanted to write by its Kurdish language served scientists and elites of his people, so we can counte Malay Gawra is one of the leaders of regenerative school interpretation of Quran.